2017
DOI: 10.1007/s00259-017-3893-z
|View full text |Cite
|
Sign up to set email alerts
|

All that glitters is not gold - new reconstruction methods using Deauville criteria for patient reporting

Abstract: If citing, it is advised that you check and use the publisher's definitive version for pagination, volume/issue, and date of publication details. And where the final published version is provided on the Research Portal, if citing you are again advised to check the publisher's website for any subsequent corrections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
36
4

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(40 citation statements)
references
References 16 publications
(14 reference statements)
0
36
4
Order By: Relevance
“…Apart from harmonising quantitative 18 F-FDG PET-CT reads, it has been reported that also visual assessment, e.g. Deauville scoring of PET-CT lymphoma studies, may be affected by a change in (reconstruction) technology and could affect patient management [25]. The observed changes (increases) in tumor-to-liver ratios for EARL2-versus EARL1-MAX41: Region-growing-based VOI using a threshold equal to 41% of SUVmax; NSCLC: Non-small cell lung cancer; PET: Positron emission tomography; PSF: Point spread function; RSNA: Radiological Society of North America; SNMMI: Society of Nuclear Medicine and Molecular Imaging; SUV: Standardised uptake value; SUV4: Region-growingbased VOI using a threshold of SUV equal to 4; SUV max : Ratio of image-derived maximum (single pixel) radioactivity concentration within a region of interest and the whole body concentration of the injected radioactivity, normalised to bodyweight; SUV mean : Ratio of image-derived average radioactivity concentration within a region of interest and the estimated whole body concentration of the injected radioactivity, normalised to bodyweight; SUV peak : Ratio of imagederived average radioactivity concentration within a 12-mm-diameter spherical volume within the region of interest, positioned to yield the highest uptake, and the whole body concentration of the injected radioactivity, normalised to bodyweight; TLG: Total lesion glycolysis equal to the MATV times SUVmean; TOF: Time of flight; VOI: Volume of interest…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Apart from harmonising quantitative 18 F-FDG PET-CT reads, it has been reported that also visual assessment, e.g. Deauville scoring of PET-CT lymphoma studies, may be affected by a change in (reconstruction) technology and could affect patient management [25]. The observed changes (increases) in tumor-to-liver ratios for EARL2-versus EARL1-MAX41: Region-growing-based VOI using a threshold equal to 41% of SUVmax; NSCLC: Non-small cell lung cancer; PET: Positron emission tomography; PSF: Point spread function; RSNA: Radiological Society of North America; SNMMI: Society of Nuclear Medicine and Molecular Imaging; SUV: Standardised uptake value; SUV4: Region-growingbased VOI using a threshold of SUV equal to 4; SUV max : Ratio of image-derived maximum (single pixel) radioactivity concentration within a region of interest and the whole body concentration of the injected radioactivity, normalised to bodyweight; SUV mean : Ratio of image-derived average radioactivity concentration within a region of interest and the estimated whole body concentration of the injected radioactivity, normalised to bodyweight; SUV peak : Ratio of imagederived average radioactivity concentration within a 12-mm-diameter spherical volume within the region of interest, positioned to yield the highest uptake, and the whole body concentration of the injected radioactivity, normalised to bodyweight; TLG: Total lesion glycolysis equal to the MATV times SUVmean; TOF: Time of flight; VOI: Volume of interest…”
Section: Discussionmentioning
confidence: 99%
“…Since then, the performance of PET-CT systems has significantly increased and new acquisition and reconstruction technologies have been introduced [23]. A change in technology may also unfavourably affect patient management when previously used quantitative and visual criteria are applied without adaptation to the new images [24,25]. The harmonisation of these newer systems would require an update of the current multicentre accreditation standards (EARL1) to accommodate higher recoveries.…”
Section: Introductionmentioning
confidence: 99%
“…Two of these patients, who had been initially diagnosed with stage III lymphoma, were quali ed to undergo selective radiation therapy due to positive PET results with remaining high activity in the axillary lymph nodes. In both cases, the follow-up PET/CT examination 3 months after radiotherapy did not show increased 18 F-FDG uptake in these lymph nodes.…”
Section: End Of Treatment Pet/ct (Epet)mentioning
confidence: 68%
“…PET/CT with 18F-uorodeoxyglucose ( 18 F-FDG) has been widely used in patients with both Hodgkin lymphoma (HL) and non-Hodgkin lymphoma (NHL) in several stages of management: for precise staging before treatment initiation [11][12][13] and for early and nal assessments of the response to chemotherapy [14]. The treatment response is evaluated by the comparison of the 18 F-FDG uptake in the lymph nodes or organs affected by lymphoma with the uptake in normal tissues. As it has been recommended by expert panels, the systematic, semi-quantitative assessment of the treatment response involves measurement of 18 F-FDG uptake expressed by SUVmax in the areas involved and in the reference regions of the liver and mediastinal blood pool (MBPS).…”
mentioning
confidence: 99%
See 1 more Smart Citation